Production Economics The Basic Theory of Production Optimisation - Rasmussen, Svend; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg Imprint: Springer, 2011)
This book covers the basic theory of how, what and when firms should produce to maximise profits. Based on the neoclassical theory of the firm presented in most general microeconomic textbooks, it extends the general treatment and focuses on the application of the theory to specific problems that the firm faces when making production decisions to maximise profits. Increasing level of government regulation and the use of specialised and often very expensive equipment in modern production motivates the following focus areas: 1) How to optimise production under restrictions., 2) Treatment of fixed inputs and the process of input fixation, 3) Optimisation of production over time, 4) Linear and Mixed Integer Programming as tools for optimisation in practice.
1 Introduction -- 2 The Production Function -- 3 Optimisation with One Input -- 4 Production and Optimisation with Two or More Inputs -- 5 Costs -- 6 Productivity, Efficiency and Technological Changes -- 7 Input Demand Functions -- 8 Land and Other Inputs -- 9 The Company's Supply Function -- 10 Optimisation of Production under Restrictions -- 11 Economies of Scale and Size -- 12 The Fixation of the Production Factors -- 13 Decreasing Sales curve -- 14 Production Over Time -- 15 Risk and Uncertainty -- 16 Economic Rent and the Value of Land -- 17 Production of Multiple Products -- 18 The Linear Programming Model -- 19 Production Planning in the Linear Programming Model - Linear Programming -- 20 Use of Linear Programming in Practical Production Planning -- Bibliography -- Appendix -- Index.
Electronic reproduction.
Keywords: Production (Economic theory).; Electronic books